Orientalism and Christian Missions: Knowledge Production and Power Relations in ABCFM Activities in Nineteenth-Century Greater Syria - Yuangga Kurnia Yahya; M. Kharis Majid; Dhiyaul Haq (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
This article examines the missionary activities of the American Board of Commissioners for Foreign Missions (ABCFM) in Greater Syria during the nineteenth century through a postcolonial perspective. Existing scholarship has largely emphasised the contribution of ABCFM to education, publishing, translation, and the Arab intellectual revival (Nahda), while paying comparatively little attention to the ways in which these activities functioned within broader structures of power and knowledge production. Employing a historical approach and drawing upon Edward Said’s theory of Orientalism, this study analyses missionary reports, official ABCFM publications, memoirs, and relevant historical literature through four analytical categories: representation, missionary legitimation, knowledge production, and power relations. The findings demonstrate that ABCFM missionaries portrayed Middle Eastern societies as communities in need of intellectual, moral, and religious reform, thereby legitimising missionary intervention. Educational institutions, medical services, translation projects, and printing activities functioned not only as instruments of evangelisation but also as mechanisms for producing knowledge and extending American Protestant intellectual and cultural influence. Through these activities, ABCFM contributed to social transformation and the development of Arab Christian communities while simultaneously establishing new forms of educational and religious authority. The study argues that Christian missions in Greater Syria should be understood as a complex arena where religion, knowledge, modernity, and power intersected and mutually shaped one another.